Deep in my heart - Arnold, Elliott 1912-1980; Courage, Alexander 1919-2008; Deutsch, Adolph 1897-1980 (Warner Home Video, 2014)
"Biographic movie about the American composer Sigmund Romberg." [imdb.com]
Original: USA 1954
Special features: Oscar nominated musical short "The Strauss fantasy" ; classic cartoon "Farm of tomorrow" ; outtake songs "Dance my darling" and "Girlies of the cabaret" ; audio only bonus "One kiss/lover come back to me" outtake
Bildformat 1.85:1 (16:9 Vollbild)
Keywords: Film; DVD-Video